2015
DOI: 10.1002/jcc.23922
|View full text |Cite
|
Sign up to set email alerts
|

The competition of Y⋯o and X⋯n halogen bonds to enhance the group V σ-hole interaction in the NCY⋯oPH3⋯NCX and OPH3⋯NCX⋯NCY (X, YF, Cl, and Br) complexes

Abstract: The positive electrostatic potentials (ESP) outside the σ-hole along the extension of OP bond in OPH3 and the negative ESP outside the nitrogen atom along the extension of the CN bond in NCX could form the Group V σ-hole interaction OPH3 ⋯NCX. In this work, the complexes NCY⋯OPH3 ⋯NCX and OPH3 ⋯NCX⋯NCY (X, YF, Cl, Br) were designed to investigate the enhancing effects of Y⋯O and X⋯N halogen bonds on the P⋯N Group V σ-hole interaction. With the addition of Y⋯O halogen bond, the VS, max values outside the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 67 publications
(93 reference statements)
1
17
0
Order By: Relevance
“…Since the pioneering work by Brinck et al, many studies have used molecular electrostatic potential maps to demonstrate the σ‐hole in possible halogen‐bond donors, see for example references . Figure shows the electrostatic potential surfaces of the halogenated methyluracil molecules studied in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pioneering work by Brinck et al, many studies have used molecular electrostatic potential maps to demonstrate the σ‐hole in possible halogen‐bond donors, see for example references . Figure shows the electrostatic potential surfaces of the halogenated methyluracil molecules studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Since the pioneering work by Brinck et al, [5,6] many studies have used molecular electrostatic potential maps to demonstrate the r-hole in possible halogen-bond donors, see for example references. [9,11,12,16,17,19,[39][40][41][42][43][44] Figure 2 shows the electrostatic potential surfaces of the halogenated methyluracil molecules studied in this work. These show the absence of a For all XmU-H 2 O systems we found a minimum with the water molecule hydrogen bonding to C4@O4.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have suggested that the QTAIM theory is very useful for studying the properties of conventional and unconventional interactions . The electron density ρ at the bond critical point (BCP) is a crucial criterion in discussing the strength of a chemical bond . The molecular graphs of Al 2 H 6 ···NH 3 and AlH 3 ···N 2 P 2 F 4 are taken as the examples and displayed in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…We observed this before, and changing the nature of the halogen atom (from Cl to Br) was listed as one of the measures to make X‐bonds stronger than hydrogen bonds in H 2 C=S• • •HOX . The increasing strength of halogen bonds involving molecules with the heavier halogens has also previously been linked with the increased σ–hole for these systems, as visualized using molecular electrostatic potential maps . We will use these features to evaluate the existence of X‐bonds in the complexes studied in this work.…”
Section: Introductionmentioning
confidence: 84%